2012
DOI: 10.1074/mcp.m111.013854
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Evaluation of Automated, Multiplexed Peptide Immunoaffinity Enrichment Coupled to Multiple Reaction Monitoring Mass Spectrometry for Quantifying Proteins in Plasma

Abstract: The inability to quantify large numbers of proteins in tissues and biofluids with high precision, sensitivity, and throughput is a major bottleneck in biomarker studies. We previously demonstrated that coupling immunoaffinity enrichment using anti-peptide antibodies (SISCAPA) to multiple reaction monitoring mass spectrometry (MRM-MS) produces Immunoprecipitation MRM-MS (immuno-MRM-MS) assays that can be multiplexed to quantify proteins in plasma with high sensitivity, specificity, and precision. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
158
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 38 publications
2
158
0
Order By: Relevance
“…Variation from the sample preparation steps was minimized through the use of [ 15 N]-IGF-1 protein, which has been demonstrated previously to improve interlaboratory agreement (33 ). The use of different instrumentation contributed to a low level of variability, while reconstitution of the reference material and method of calibration were identified as the primary source of interlaboratory variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation from the sample preparation steps was minimized through the use of [ 15 N]-IGF-1 protein, which has been demonstrated previously to improve interlaboratory agreement (33 ). The use of different instrumentation contributed to a low level of variability, while reconstitution of the reference material and method of calibration were identified as the primary source of interlaboratory variation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when unfractionated plasma was digested with trypsin and supplemented with predigested, purified proteins and stable isotope-labeled peptide internal standards, the interlaboratory imprecision was Ͻ32% (31,32 ). More recently, interlaboratory imprecision was evaluated for the SISCAPA (Stable Isotope Standards and Capture by Anti-Peptide Antibodies) method of protein quantification (33 ). When unfractionated plasma was supplemented with protein standards, digested, and quantified by use of the SISCAPA method, the imprecision was Ͻ14%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, currently available approaches typically rely on the use of a single reference peptide or tag that is spiked early in the analytical process. Although such a reference tag corrects for the concomitant loss in endogenous peptides during sample digestion and fractionation and thus increases accuracy and reproducibility 20,21 , the use of only one reference tag requires that the quantification of each protein standard be accomplished separately. This ultimately adds avoidable steps into the workflow, potentially introducing undesirable artifacts (Supplementary Table 1).…”
mentioning
confidence: 99%
“…Targeted proteomics is best suited to meet these needs. Multiple studies clearly demonstrated the reproducibility of SRM‐MS across laboratories 29, 30. SRM‐MS has been applied to quantify protein levels of liver tissue across 40 strains of BDX mouse 31 and quantitative trait analysis (QTL) of 78 Saccharomyces cerevisiae strains 32.…”
Section: Introductionmentioning
confidence: 99%